A strain of Lactobacillus plantarum from piglet intestines enhances the anti-PoRV effect via the STING-IFN-I pathway - Anqi Sun; Xin Shan; Ruihan Liu; Zhengxu Tang; Jingshu Huang; Shihan Zhang; Lihong Bian; Yumeng Shi; Zixuan Liu; Jingtao Hu; Chunfeng Wang (BMC Veterinary Research)
Abstract Background Rotavirus infection represents a major etiology of severe diarrheal disease in neonatal and weaned piglets, causing substantial economic burdens to the global swine industry. Lactobacillus plantarum, a ubiquitous probiotic in natural ecosystems, has demonstrated multifaceted biological functions. The stimulator of the interferon gene (STING) is involved in type I interferon (IFN-I) mediated host antiviral innate immunity, which is a pivotal adaptor in response to the microbial DNA/RNA-activated signaling pathways. Emerging evidence suggests that certain probiotic strains can activate the STING-dependent pathway to induce IFN-I responses. In the present study, we successfully isolated a strain of Lactobacillus plantarum (designated LP1)from porcine intestinal contents and investigate its potential to counteract porcine rotavirus (PoRV) infection via modulation of antiviral signaling pathway. Result LP1 exhibited superior tolerance to simulated gastrointestinal conditions (pH 3.0 and 0.3% bile salts) compared with other isolated Lactobacillus strains. In vitro adhesion assays demonstrated that LP1effectively colonized porcine intestinal epithelial cells (IPEC-J2) without inducing cytotoxicity or apoptosis. Animal experiments also confirmed the protective effect of LP1 in mice against rotavirus, by reducing body weight loss, promoting viral clearance in feces, and alleviating intestinal mucosal damage. Mechanistic investigations identified STING-IRF3 pathway activation as the pivotal antiviral mechanism. Both phosphorylation of STING and IRF3 in LP1-treated IPEC-J2 cells accompanied by upregulated transcription and secretion of IFN-β and interferon-stimulated genes (ISGs). Consistent findings were observed in intestinal tissues of LP1-protected mice with STING pathway activation correlating with reduction in viral titers. Crucially, STING inhibitor (C-170) administration could reverse LP1-mediated antiviral effects. Conclusion LP1 exerts potent anti-PoRV activity in both murine models and porcine intestinal epithelial (IPEC-J2) cells through STING-IRF3 signaling axis-mediated IFN-β production.